Simulation of Void Detection System using Gamma-Ray Compton Scattering Technique - Sari, Mona Berlian; Wirawan, Rahadi; Waris, Abdul; Kim, Hong Joo; Djamal, Mitra (ITB Journal Publisher, LPPM ITB, 2019)
A simple void detection system for concrete was successfully developed using high-penetration gamma rays with Compton scattering. This research attempted to identify a void in the subsurface of a concrete volume that could not be accessed from any of the sides. Monte Carlo simulation using GEANT4 toolkit was performed to investigate the gamma-ray backscattering events. An NaI(Tl) detector was used with 60Co and 137Cs as gamma-ray sources. The void?s location was successfully detected during material target scanning. Density discrepancies conduce variance of the backscattering peak produced due to the presence of a void. Compared to 60Co as the gamma-ray source, 137Cs is a better choice for application in NDT systems using Compton scattering.